FAKTOR FAKTOR YANG MEMPENGARUHI FINANCIAL PERFORMANCE PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Arpin Baresi Putra; Augustpaosa Nariman (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The main purpose of this study was to determine the effect of Profitability, Financial Leverage, and Environmental Performance on Financial Performance. This study used 26 samples of manufacturing companies as research subjects after going through a selection process using purposive sampling. The data in this study were processed using Eviews 12 and Microsoft Excel. The results of this study indicate that Profitability has a positive and significant effect on Financial Performance, Financial Leverage has a positive and significant effect on Financial Performance, and Environmental Performance has a negative and insignificant effect on Financial.